The ideology towards English as a medium of instruction (EMI) adoption in higher education in Malaysia : a case study - Rahman, Mohammad Mosiur; Manjet Kaur Mehar Singh, (Penerbit Universiti Kebangsaan Malaysia, 2022)
English as a medium of instruction (EMI) has been implemented in the context of higher education in non-native English-speaking countries mainly to attract international students through internationalisation while helping local students achieve success in the job market and pursue further education both locally and globally. In the context of Malaysian higher education, Malay has been adopted as the medium of instruction (MOI) and should be implemented in public and private universities. However, EMI has been adopted for some of the programs in public universities, and private universities adopted English as their MOI. Therefore, the purpose of this case study is to uncover the institutional (university language policy) and individual level (lecturers) ideologies about English and EMI adoption in a public research university (Purple University, pseudonym) in Malaysia. Data were collected from the two oldest and largest schools of the university with an emphasis on undergraduate degrees, the School of Management and the School of Industrial Technology. In order to establish triangulation in the data collection methods, data were collected through interviews with lecturers and content analysis of university websites, admission requirements in the EMI program, and curriculum analysis. Six themes emerged from the findings of the study, including English as the language of choice for MOI, EMI and the internationalisation of higher education, English as an academic language, the role of EMI in the development of English language communication, and the economic and social relevance of English in Malaysia. The study also revealed that despite the lack of a defined language policy governing the use of English in Malaysia, there is agreement on the adoption of EMI at the meso and microlevel stakeholders of the university.